Investigating the Role of Altered Energy Metabolism in the Therapeutic Response of Rectal Cancer - Buckley, Croí-Ellyn (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2022)
Colorectal cancer (CRC) is the 3rd most commonly diagnosed cancer world-wide, accounting for an estimated 10% of all cancers diagnosed annually globally. One in three CRCs occur in the rectum. The standard of care for locally-advanced rectal cancer (LARC) treatment is neoadjuvant chemoradiation therapy (neoCRT), followed by surgery. Unfortunately, resistance to neoCRT is a significant clinical problem in the management of rectal cancer, with only an estimated 15-30% of rectal cancer patients achieving a complete pathological response (pCR). Therefore, there is an urgent unmet need to identify underlying mechanisms of treatment resistance and novel treatment strategies to improve response in rectal cancer. In recent years, altered tumour energy metabolism has been demonstrated to be associated with radioresistance in cancer, but its role in rectal cancer is incompletely understood. In this thesis, the role of altered tumour energy metabolism in rectal adenocarcinoma and the potential of metformin, a clinically-approved anti-diabetic drug and metabolic modulator, as a novel radiosensitiser was investigated in rectal cancer. SW837 rectal cancer cells and HCT116 colon cancer cells were identified as an in vitro model of inherent radioresistance/radiosensitivity. SW837 cells were significantly more resistant to fluorouracil (5-FU) cytotoxicity, when compared to HCT116 cells. To identify potential underlying mechanisms of radioresistance in this model, HCT116 and SW837 cells were characterised in terms of multiple parameters frequently implicated in radioresistance. Radiosensitive HCT116 cells displayed significantly elevated proliferative rates, a more radiosensitive basal cell cycle distribution and induced G2/M arrest earlier following irradiation with clinically-relevant doses of X-ray radiation, when compared to radioresistant SW837 cells. In addition, radioresistant SW837 cells displayed more efficient repair of radiation-induced DNA damage, and a reduced reliance on glycolysis, when compared to HCT116 cells. Transcriptomic profiling of HCT116 and SW837 cells demonstrated a significantly altered transcriptome in SW837 cells, when compared to HCT116 cells. In addition, ingenuity pathway analysis (IPA) of transcriptomic data demonstrated significant alterations in pathways commonly associated with radioresponse, in SW837 cells including cell cycle, DNA damage repair, oxidative stress and metabolism, including significant upregulation of oxidative phosphorylation related genes. As hypoxia is a common feature of solid malignancies, and contributes to the development of radioresistance, the inherent model of radioresistant and radiosensitive CRC was characterised under hypoxic (0.5% O2) conditions. SW837 cells remained significantly more radioresistant, when compared to HCT116 cells under hypoxia (0.5% O2). Enhanced radiation-induced apoptosis was demonstrated in HCT116 cells under hypoxia (0.5% O2). Hypoxic exposure was demonstrated to significantly alter cell cycle distribution and phenotype in both HCT116 and SW837 cells. Radiation-induced DNA damage was efficiently repaired under hypoxic conditions in both cell lines. Hypoxia was demonstrated to decrease oxidative phosphorylation and increase glycolysis in both HCT116 and SW837 cells. The effect of inhibition of metabolism on radioresponse was assessed in HCT116 and SW837 cells. A novel drug, Pyrazinib (P3), which was previously demonstrated to act as an anti-metabolic radiosensitiser in oesophageal cancer was demonstrated to significantly inhibit oxidative phosphorylation and glycolysis, and induce mitochondrial dysfunction in SW837 cells. However, P3 did not radiosensitise HCT116 or SW837 cells under normoxic or hypoxic conditions. Metformin, a clinically approved drug in the management of diabetes, and an inhibitor of complex I of the electron transport chain, was demonstrated to significantly inhibit oxidative phosphorylation in HCT116 and SW837 cells, and induce mitochondrial dysfunction. Metformin treatment was demonstrated to significantly radiosensitise HCT116 and SW837 cells to clinically-relevant doses of 1.8 Gy radiation, and was superior to 5-FU, which is the current standard of care. The potential mechanisms of metformin-induced radiosensitisation were subsequently assessed. Metformin was demonstrated to affect cell cycle distribution and progression following radiation in HCT116 and SW837 cells. Metformin treatment induced DNA damage, inhibited DNA damage repair, induced cell death and increased glutathione levels in CRC cells. Metformin significantly altered the transcriptome of SW837 cells, altering pathways related to metabolism, DNA damage repair and oxidative stress. Metformin treatment significantly inhibited oxidative phosphorylation and glycolysis in pre-treatment rectal cancer biopsies, but did not alter metabolism in non-cancer rectal tissue. Metformin also induced the secretion of inflammatory proteins from rectal cancer and non-cancer rectal tissue. Metabolomic profiling of pre-treatment rectal cancer sera identified 16 metabolites significantly associated with pathological response to neoCRT (tumour regression score) (TRS). Metabolomic profiling of pre-treatment rectal cancer biopsies and tumour conditioned media (TCM) demonstrated significant correlations with clinicopathological features, including TRS. Transcriptomic profiling of pre-treatment rectal tumour biopsies demonstrated significant alterations in gene expression between patients with a good response (TRS 0) and poor response (TRS 2) to treatment and in patients with a pathological tumour (T) stage of T3/4, when compared to those with a pathological T stage T0. IPA analysis of transcriptomic data also demonstrated significant alterations to metabolic pathways in patients with a pathological T stage of T3/4, when compared to those with T0. Real-time metabolic phenotyping of rectal tumour and non-cancer rectal tissue demonstrated significantly elevated oxidative phosphorylation levels, when compared to glycolysis. Metabolomic profiling of non-cancer rectal tissue and rectal cancer tissue demonstrated 23 metabolites, primarily phosphatidylcholines, significantly altered in rectal cancer tissue, and four metabolites significantly altered in TCM, when compared to non-cancer conditioned media (NCM). The protein secretome of rectal cancer was significantly altered, when compared to non-cancer tissue, as assessed by multi-plex ELISA. Transcriptomic profiling demonstrated significant alterations to the metabolome of rectal cancer, when compared to non-cancer rectal tissue, including alterations to metabolic pathways. Hierarchical clustering analysis demonstrated accurate clustering into cancer and non-cancer cohorts using combined metabolomic and transcriptomic data. Together this thesis demonstrates altered energy metabolism in the development and therapeutic response of rectal cancer, highlighting the potential role of metabolic markers as predictive biomarkers of treatment response in rectal cancer. Importantly, the potential utility of metformin, as a novel anti-metabolic radiosensitiser in rectal cancer, to boost patient response to treatment, is also demonstrated.
APPROVED
Keywords: Colorectal Cancer; Rectal Cancer; Radiation therapy; Radioresistance; Metabolism; Oxidative Phosphorylation